Hommage à François Gros, savant engagé - Chevènement, Jean-Pierre; Lazar, Philippe; Papon, Pierre; Gallois, Louis (Comptes Rendus Biologies, 2024)
As an eminent scientist, fully aware of his social responsibilities, François Gros has been consulted on several occasions on how to make better use of science in the service of society. One of the first reports asked of him was by President Giscard d’Estaing on the social and industrial consequences of the rise of biology (1979). A few years later, at the request of President François Mitterrand, he chaired the National Conference on Research and Technology (1981–1982), which led to substantial changes in the way French public research was organised.